Velocity map imaging of HBr photodissociation in large rare gas clusters - Fedor, J; Kocisek, J; Poterya, V; Votava, O; Pysanenko, A; Lipciuc, M L; Kitsopoulos, T N; Fárník, M (The Journal of chemical physics, 2011)
We have implemented the velocity map imaging technique to study clustering in the pulsed supersonic expansions of hydrogen bromide in helium, argon, and xenon. The expansions are characterized by direct imaging of the beam velocity distributions. We have investigated the cluster generation by means of UV photodissociation and photoionization of HBr molecules. Two distinct features appear in the hydrogen atom photofragment images in the clustering regime: (i) photofragments with near zero kinetic energies and (ii) "hot" photofragments originating from vibrationally excited HBr molecules. The origin of both features is attributed to the fragment caging by the cluster. We discuss the nature of the formed clusters based on the change of the photofragment images with the expansion parameters and on the photoionization mass spectra and conclude that single HBr molecule encompassed with rare gas "snowball" is consistent with the experimental observations.